Nanoplastics impacts on Thiobacillus denitrificans: Effects of size and dissolved organic matter. (1st July 2023) - Li, Yuancheng; Guo, Chuling; Zhang, Siyu; Ke, Changdong; Deng, Yanping; Dang, Zhi
Abstract: The widespread distribution of nanoplastics and dissolved organic matter (DOM) in sewage raises concerns about the potential impact of DOM on the bioavailability of nanoplastics. In this study, the effects of different sizes (100 nm and 350 nm) of polystyrene nanoplastics (PS-NPs, 50 mg/L) and combined with 10 mg/L or 50 mg/L DOMs (fulvic acid, humic acid and sodium alginate) on the growth and denitrification ability of Thiobacillus denitrificans were investigated. Results showed that 100 nm PS-NPs (50 mg/L) cause a longer delay in the nitrate reduction (3 days) of T. denitrificans than 350 nm PS-NPs (2 days). Furthermore, the presence of DOM exacerbated the adverse effect of 100 nm PS-NPs on denitrification, resulting in a delay of 1–4 days to complete denitrification. Fulvic acid (50 mg/L) and humic acid (50 mg/L) had the most significant adverse effect on increasing 100 nm PS-NPs (50 mg/L), causing a reduction of 20 mmol/L nitrate by T. denitrificans in nearly 7 days. It is noteworthy that the presence of DOM did not modify the adverse effect of 350 nm PS-NPs on denitrification. Further analysis of toxicity mechanism of PS-NPs revealed that they could induce reactive oxygen species (ROS) and suppressed denitrification gene expression. The results suggested that DOM may assist in the cellular internalization of PS-NPs by inhibiting PS-NPs aggregation, leading to the increased ROS levels and accelerated T. denitrificans death. This study highlights the potential risk of nanoplastics to autotrophic denitrifying bacteria in the presence of DOM and provides new insights for the treatment of nitrogen-containing wastewater by T. denitrificans . Graphical abstract: Image 1 Highlights: The dissolved organic matter altered the biological toxicity of 100 nm polystyrene nanoplastics (PS-NPs). The effect of PS-NPs on T. denitrificans mainly depended on its concentration and size. The toxic mechanism of PS-NPs to T. denitrificans was oxidative stress. PS-NPs inhibited the related reduction genes in T. denitrificans.